BIncidence of Hepatitis B in patients screened before Felxible Nasolaryngoscopy in Mayo Hospital, Lahore (Journal of Fatima Jinnah Medical University, 2018)
Purpose: To assess the incidence of hepatitis B infection in patients before flexible fiberoptic nasolaryngoscopy for dysphonia.Materials and Method: This prospective cross-sectional study was conducted at Mayo hospital Lahore from May 2013 to May 2014. All dysphonic patients who fulfilled inclusion criterion for flexible nasolaryngoscopy were screened for HepatitisB as part of infection surveillance& control. A proforma was designed for collection of data and consent was obtained from all patients before inclusion in study. Every patient was serologically screened by rapid chromatography immunoassay (ICT) for qualitative detection of hepatitis B antibodies in patients before fiberoptic nasolaryngoscopy.Setting:ENT Unit-1 Mayo Hospital affiliated with King Edward Medical University, LahoreResults: Three hundred patients (300) who had been planned for flexible nasolaryngoscopy were screened for Hepatitis B. Among three hundred patients 180 (60 %) were males and 120 (40 %) were females. 24 patients (08 %) diagnosed serologically positive for hepatitis B. Among hepatitis B positive patients nine (37.5%) were females and fifteen (62.5 % ) were males.Conclusion: The incidence of hepatitis B is high in our society and most of them diagnosed on routine screening test before flexible nasolaryngoscopy. With this incidence continuously on the rise, urgent interventions needto be done for earlier diagnosis and prevention in order to reduce the mortality and loss of medical resources linked with this disease in larger public interest